Report on the piloting of a curriculum in technology education for primary and lower secondary students in the CARICOM - Gift, Edrick (CARICOM Secretariat GeorgetownGY, 2004)
Presents the outcome of the piloting exercise. Provides a summary of results from Barbados, Jamaica and the Bahamas. Summarizes the comments from free responses of secondary teachers from the three territories. Makes recommendations.